2014
DOI: 10.1016/j.rboe.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Radiological analysis on femoral tunnel positioning between isometric and anatomical reconstructions of the anterior cruciate ligament

Abstract: Objectivethe aim of this study was to radiologically evaluate the femoral tunnel position in anterior cruciate ligament (ACL) reconstructions using the isometric and anatomical techniques.Methodsa prospective analytical study was conducted on patients undergoing ACL reconstruction by means of the isometric and anatomical techniques, using grafts from the knee flexor tendons or patellar tendon. Twenty-eight patients were recruited during the immediate postoperative period, at the knee surgery outpatient clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…In this study, the mean difference between the angles was 16.8°. However, unlike the present study, Vieira et al 14 measured the inclination of the tunnels in relation to the anatomical axis of the femur.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this study, the mean difference between the angles was 16.8°. However, unlike the present study, Vieira et al 14 measured the inclination of the tunnels in relation to the anatomical axis of the femur.…”
Section: Discussionmentioning
confidence: 57%
“… 12 A study by Aglietti et al 13 demonstrated that the two-incision technique presented a significantly lower mean femoral angle in the AP X-ray (37°) when compared with the one-incision technique (68°). Vieira et al 14 observed that the angles in anatomical reconstructions are smaller than in transtibial procedures, as the former have a more horizontal orientation. The mean difference between the tunnel angles, measured on X-rays, was 16.74°.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with recent studies, in which the gliding on maximum extension was similar in both techniques. 28 , 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) imaging techniques, like computerized tomography (CT) and magnetic resonance imaging (MRI) are now commonly used to evaluate ACL injury and progress following ACL reconstruction [ 11 ]. Nevertheless two-dimensional (2D) imaging measurements, such as BL on plain x-rays, remain the most common technique for estimating the position of the distal femoral tunnel [ 10 , 13 – 18 ], due to its simplicity, easy access, availability, low radiation exposure and low costs. Spatial orientation of the knee joint in the X-ray setup may affect the comparative position of landmarks in a 2D image [ 11 ].…”
Section: Introductionmentioning
confidence: 99%